The application of term mining techniques and fuzzy proximity for driving force study in lean management. (October 2020) - Jing, Shuwei; Luo, Pengfei; Niu, Zhanwen; Yan, Junai; Ho, Zih-Ping
Highlights: This paper proposes a driving force analysis system, named TMT-FP. TMT-FP can help decision makers to design a scientific promotion mechanism. TMT-FP can help enterprise to improve its management innovation level. Abstract: Driving force analysis of participants bringing on the process of management innovation can help managers to make decisions in lean management implementation. Traditional researches have verified the importance of participation in management innovation and lean management, but have not further analyzed the driving force of participants. Therefore, this paper presents a general framework for driving force analysis, combining the terms mining technique (TMT) and fuzzy proximity (FP), named TMT-FP, and applies it to analyze the driving force of participants on the management innovation process in the case enterprise. In the first phase of the methodology, the terms mining technique (TMT) is used to analyze the results of interview cases from enterprises, and to discern participant's character patterns in the management innovation process. The second phase of the methodology, Fuzzy proximity (FP) is used to build assessment methods of the driving force for participants in lean management implementation. Finally, this paper analyzes a case from the interviewed enterprises using the terms mining technique and fuzzy proximity (TMT-FP) analysis system. The results indicate that senior leaders and third-party lean experts have the greatest driving effect on management innovation comparing with basic production personnel in the case enterprise. At the same time, the results show that a TMT-FP analysis system can effectively analyze the driving force of participants and help decision makers to design a scientific promotion mechanism in lean management. In summary, this paper proposes a new driving force analysis system for lean management participants, the results of driving force evaluation obtained by this system can help the case enterprise to improve its management innovation level.